Reply to Klonoff et al. Limitations of a Recent Study on Insulin Pen Needle Preferences in People with Diabetes. Comment on “Gentile et al. Enhancing Insulin Therapy Adherence Through Technology: Which Needles Do People with Diabetes Prefer? Diabetology 2026, 7, 56” - Sandro Gentile; Raffaella Fiorentino; Maddalena Lettieri; Giuseppina Guarino; Giampiero Marino; Elisabetta Tommasi; Vera Frison; Ersilia Satta; Maria Chiarello; Giuseppe Caccavale; Emilia Masuccio; Felice Strollo (Diabetology, 2026)
This response letter addresses criticisms from a recent commentary regarding a real-world survey on insulin pen needle preferences. The authors clarify that their study was purposefully designed as an observational survey to capture genuine patient perceptions under routine clinical conditions, rather than functioning as a randomized controlled trial. Consequently, methodological constraints such as blinding were fundamentally inapplicable. Furthermore, the authors emphasize the limited relevance of the Hawthorne effect in this context. While originally described in industrial settings, recent systematic reviews in the medical literature indicate that its magnitude and impact on modern clinical research are highly uncertain and generally modest. Ultimately, the study effectively highlights real-world patient experiences with the shortest and thinnest needles currently available, aligning with advances in injection technology.